World War 1 in Colour - Jonathan Martin; Branagh, Kenneth, 1960-; Emperor Franz Josef; Tsar Nicholas II (UK Capital Entertainment, 2003)
With all the incredible World War II documentaries out there, it is pretty amazing how few World War I documentaries there are, let alone quality ones. Part may be from the minimal amount of archival footage, much of which is really rough, and the fact that most of the veterans died before having the chance to tell their stories on color film. But as Ken Burns has taught us, none of these elements are necessary to create great documentaries. All you need is a little creativity, scholarly and dramatic content, and a sharp presentation. World War 1 in Color is one of those documentaries. Narrated by Sir Kenneth Branagh, World War 1 in Color does a great job presenting this important time in world history in a way that is both academic and heart wrenching, with a modernized presentation. Lasting from 1914-1918 and involving 68 million soldiers, WWI was the first modern war and set the historical course for the entire 20th century. On one hand, it ended many old concepts of battle and gallantry that existed in Europe for centuries. On the other hand, it introduced many modern elements of war including grand multinational involvement and technological innovation including the use of submarines, air warfare, trenches, and chemical weaponry. The big selling point of this DVD is obviously the colorization of the archival footage, which is fascinating and does bring a shocking realism to the war. But it is important to note the colorization never comes off as a gimmick, nor does it overshadow the high quality of this documentary. World War 1 in Color is broken up into six episodes; "Catastrophe" (the cause and start of WWI), "Slaughter in the Trenches" (the great stalemate of the German, French and British ground troops on the western front), "Blood in the Air" (the story of the introduction of air warfare), "Killers of the Sea" (innovation in sea battle including the use of the submarine), "Mayhem on the Eastern Front" (the political and military chaos with the Germans, Austrians and Russians), and "Victory and Despair" (1918, the costliest year of the war; America's involvement; the end of the stalemate on the western front; the end of the war; and the Treaty of Versailles). If you are looking for a strong overview and starting point to learn about WWI look no further than World War 1 in Color. It is quite impressive.
Language(s): English Subtitle(s): No Subtitle
Keywords: Documentary